Professional and Elite Young Soccer Players: Differences in Functional Movement ScreenTM Values - Italo Sannicandro; Giacomo Cofano; Rosario D'Onofrio; Andrea Piccinno (Physical Education and Sports: Studies and Research, 2023)
Background: Soccer is a sport that requires very complex movements performed at high speeds: running, jumping, decelerating, changing direction or running direction, and kicking are complex movements that require high control and significant joint stability at all ages. Control of the body and individual body districts becomes important for both performance and injury prevention. Objective: This study aims to verify the Functional Movement Screen (FMSTM) values in different categories of players, from the youth leagues to professional soccer players. Methods: A sample of soccer players (n=112) took part in the study. The sample was subdivided according to their category, resulting in the following subgroups: a) professional soccer players (PSP, n=56,), Under 19 - Primavera (U19, n=29), Under 17 (U17, n=27). The FMS protocol was used to assess the seven functional movements and the associated risk of non-contact injury. Results: Statistically significant differences emerged in the total scores between the U17 group and the PSP group (14.8±2.9 vs 19.1±1.4, p<0.01), between the U17 group and the Under 19 - Primavera group (14.8±2.9 vs 16.2±2.1, p<0.05) and between the Under 19 - Primavera group and the PSP (16.2±2.1 vs 19.1±1.4, p<0.01). Conclusion: The values obtained show that young soccer players have a very different qualitative control of movement than highly qualified players. This study shows significant differences not only between the total scores, but more importantly between the individual 7 assessment tests that the FMS protocol includes: these values provide insight into which movements should receive more attention in athletic conditioning in the youth sector.